Socio-economic determinants of SARS-CoV-2 infection: Results from a population-based cross-sectional serosurvey in Geneva, Switzerland - Santa-Ramírez, Hugo-Alejandro; Wisniak, Ania; Pullen, Nick; Zaballa, María-Eugenia; Pennacchio, Francesco; Lorthe, Elsa; Dumont, Roxane; Baysson, Hélène; Guessous, Idris; Stringhini, Silvia (Frontiers in Public Health, 2022)
Background SARS-CoV-2 infection and its health consequences have disproportionally affected disadvantaged socio-economic groups globally. This study aimed to analyze the association between socio-economic conditions and having developed antibodies for SARS-CoV-2 in a population-based sample in the canton of Geneva, Switzerland. Methods Data was obtained from a population-based serosurvey of adults in Geneva and their household members, between November and December, 2020, towards the end of the second pandemic wave in the canton. Participants were tested for antibodies for SARS-CoV-2. Socio-economic conditions representing different dimensions were self-reported. Mixed effects logistic regressions were conducted for each predictor to test its association with seropositive status as the main outcome. Results Retired participants and those living in suburban areas had lower odds of a seropositive result when compared to employed participants (OR 0.42, 95% CI - 0.20 – 0.87) and those living in urban areas (OR 0.67, 95% CI - 0.46 – 0.97), respectively. People facing financial hardship for less than a year had higher odds of a seropositive result compared to those who had never faced them (OR 2.23, 95% CI - 1.01 – 4.95). Educational level, occupational position and household income were not associated with being seropositive, nor were ethnicity or country of birth. Discussion While conventional measures of socio-economic status did not seem to be related to the risk of being infected in this sample, this study sheds lights on the importance of examining the broader social determinants of health when evaluating the differential impact of the pandemic within the population.